Space for Innovation for Sustainable Community-Based Biofuel Production and Use: Lessons Learned for Policy from Nhambita Community, Mozambique - Schut, Marc; van Paassen, Annemarie; Leeuwis, Cees; Bos, Sandra; Leonardo, Wilson; Lerner, Anna (2012)
This paper provides insights and recommendations for policy on the opportunities and constrains that influence the space for innovation for sustainable community-based biofuel production and use. Promoted by the Mozambican government, Nhambita community established jatropha trials in 2005. Initial results were promising, but crop failure and the absence of organized markets led to scepticism amongst farmers. We start from the idea that the promotion of community-based biofuel production and use requires taking interactions between social-cultural, biophysical, economic, political, and legal subsystems across different scales and levels of analysis through time into account. Our analysis demonstrates that heterogeneous farming strategies and their synergies at community level should be carefully assessed. Furthermore, national and international political and legal developments, such as the development of biofuel sustainability criteria, influence the local space in which community-based biofuel developments take place. We conclude that ex-ante integrated assessment and creating an enabling environment can enhance space for sustainable community-based biofuel production and use. It may provide insights into the opportunities and constraints for different types of smallholders, and promote the development of adequate policy mechanisms to prevent biofuels from becoming a threat rather than an opportunity for smallholders.